(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Madayantika (Lawsonia inermis Linn.) is a miracle medicinal plant used in the treatment of various skin diseases especially in wound healing activity in the Indian system of medicine. Aim and Objective: The objective of the study presented in this article was to evaluate the wound healing potential of aqueous extract. The models usually used for evaluation of wound healing activity are Excision wound model, Incision Wound Model and Dead Space model. Among those excisions wound model is selected for the study. Healthy wistar strain Albino rats of either sex weighing 150-200gm were used for the study. Animals are acclimatized in a laboratory and then it were anaesthetized and then dorsal surface of rats were shaved to about an area of 500mm2 and then it was cut carefully with sterilized forceps and left undressed for open environment, then extracts of test drugs, Scaffolds containing aqueous extract and standard drug were applied and then observed and noted. Results: The extract of Madayantika (Lawsonia inermis Linn.) treated wounds were found to epithelize faster and rate of wound contraction was significantly (p<0.0001) increased as compared to control group (p< 0.01). The extract treated animals showed from 502 ±0.364 to 25.1±0.252 reduction in wound area when compared with control groups from 502± 0.538 to 40.71± 0.166. Conclusion: Madayantika (Lawsonia inermis Linn.) possess significant wound healing effect which may beneficial in treating wounds. This drug showed extremely significant results in wound healing activity.